Brain derived neurotrophic factor expression and DNA methylation in response to subchronic valproic acid and/or aldosterone treatment - Buzgoova, Katarina (Croat Med J, 2019)
AIM: To test the hypothesis that valproic acid treatment positively affects brain-derived neurotrophic factor (BDNF) expression and DNA methylation in the hippocampus and brain cortex of rats simultaneously treated with aldosterone. METHODS: Male Sprague-Dawley rats (N = 40) were treated for two weeks with valproic acid (100 mg/1 kg body weight/day) in drinking water and aldosterone (2 μg/100 g body weight/day) or placebo via subcutaneous osmotic minipumps. RESULTS: Treatment with valproic acid did not modify BDNF gene expression in the hippocampus but reduced BDNF mRNA levels in the brain cortex. Valproic acid treatment marginally enhanced global DNA methylation in the frontal cortex. BDNF expression negatively correlated with DNA methylation in the hippocampus of valproic acid-treated rats. An unexpected finding was that aldosterone treatment significantly decreased global DNA methylation in the hippocampus. CONCLUSION: The effect of valproic acid on BDNF expression in the brain may depend on the extent of pathological changes present at the time of treatment onset. The observed negative correlation between BDNF expression and DNA methylation in the hippocampus of valproic acid-treated rats encourages further studies.